Molecular Diagnosis of Alexander Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The value of clinical and MRI criteria in the diagnosis of Alexander disease was determined by using GFAP gene sequencing as the confirmatory assay in 13 patients with variable ages of onset in a study at Children's National Medical Center, Washington, DC and other centers.